Rough Multilinear Fractional Integrals on Weighted Morrey Spaces. (3rd August 2015) - Li, Xiao; Cui, Runqing
Abstract : It is showed that a class of multilinear fractional operators with rough kernels, which are similar to the higher-order commutators for the rough fractional integrals, are bounded on the weighted Morrey spaces.